PENGARUH PENGALAMAN, INDEPENDENSI, SKEPTISISME PROFESIONAL AUDITOR PADA PENDETEKSIAN KECURANGAN - Siantari, Yessy Angelita; Noviyanti, Suzy (Jurnal Akuntansi, 2024)
Public accountants have vital responsible to ensure financial report quality by their competencies, skill and integrity so this study purposes is to understand effect auditor experience, independence and professional skepticism on fraud detection. This study was conducted in Central Java Accounting Office and collected data using questionnaire by 37 auditors. Data analysis technique is multiple linear regression and using SPSS Software. The result shows auditor experience, independence and professional skepticism positive significant on fraud detection and auditor independence is the most dominant variable. Research limitation is questionnaire could not portrait auditor behavior deeply so further study could combine questionnaire and interview.